Using Next-Generation Sequencing Technology to Explore Genetic Pathways in Endophytic Fungi in the Syntheses of Plant Bioactive Metabolites - Bielecka, Monika; Pencakowski, Bartosz; Nicoletti, Rosario (Agriculture (Basel), 2022)
Recent investigations carried out all over the world have disclosed the capacity of a multitude of endophytic fungal species/strains to produce bioactive compounds which are the same or structurally related to those synthesized by their host plants. This intriguing phenomenon has implemented huge research activity aimed at ascertaining the nature of the biological processes underlying this convergence, as well as to characterize the genetic bases of the biosynthetic schemes. Insights on these basic issues may support the biotechnological exploitation of wild strains, and their eventual improvement through genome editing. Aspects concerning the use of next generation sequencing technologies for the comparative elucidation of the biosynthetic pathways operating in endophytic fungi and their host plants are reviewed in this paper in view of applicative perspectives. Our literature search yielded 21 references dealing with at least 26 strains which have been the subject of experimental activities involving massively parallel genome and transcriptome sequencing methods in the last eight years.